2010
DOI: 10.3155/1047-3289.60.12.1410
|View full text |Cite
|
Sign up to set email alerts
|

Modification in the Soil and Traffic-Related Sources of Particle Matter between 1998 and 2007 in Santiago de Chile

Abstract: Santiago de Chile is one of the most polluted South American cities, concentrating its pollution episodes during winter. Daily PM 2.5 (particulate matter [PM] Յ 2.5 m in aerodynamic diameter) concentrations over 80 g/m 3 have been reached frequently since 1998. Despite several regulations introduced over the past 20 yr to improve the air quality, PM concentration levels remain high. In this work, sampling in downtown Santiago was conducted from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 17 publications
6
36
0
Order By: Relevance
“…Second, the relationship leveled off at high PBF consumption values, which occurred in the most recent years when there were cleaner fuels available and newer cars that boast cleaner emission profiles. This is consistent with findings from a factor analysis study, which showed that motor vehicles were becoming a less prominent source of PM 2.5 due to an improved vehicle fleet (Moreno et al, 2010). Therefore, it is plausible that each unit of PBF consumption was associated with lower PM 2.5 emissions in more recent years, leading to the weaker relationship at higher consumption levels.…”
Section: Impact Of Fuel Sales On Trendssupporting
confidence: 87%
See 1 more Smart Citation
“…Second, the relationship leveled off at high PBF consumption values, which occurred in the most recent years when there were cleaner fuels available and newer cars that boast cleaner emission profiles. This is consistent with findings from a factor analysis study, which showed that motor vehicles were becoming a less prominent source of PM 2.5 due to an improved vehicle fleet (Moreno et al, 2010). Therefore, it is plausible that each unit of PBF consumption was associated with lower PM 2.5 emissions in more recent years, leading to the weaker relationship at higher consumption levels.…”
Section: Impact Of Fuel Sales On Trendssupporting
confidence: 87%
“…The meteorology-adjusted PM 2.5 concentrations were lower by 21.8 mg/m 3 in 2009/2010compared to 1998. While there was an overall steady decline in PM 2.5 levels in 1998 to 2010, there was a surge in annual concentrations between 2005 and 2008; during this period, annual adjusted PM 2.5 concentrations peaked in 2007, representing a total increase of 7.9 mg/m 3 in two consecutive years.…”
Section: Pm 25 Regression Modelmentioning
confidence: 78%
“…The only components that seem to have increased in proportion after 2005 are organic and black carbon. This increase is consistent with the growth in the number of vehicles in Santiago de Chile (Moreno et al, 2010). It has to be noted that measurements of organic carbon in 2003 and 2005 were performed with thermo-optical methods (Ambient Carbon Particulate Monitor 5400, from Rupprecht and Patashnick Co.).…”
Section: Time Seriessupporting
confidence: 76%
“…The level of knowledge concerning emission sources in Santiago is reasonable, but the emission profile is expected to be under continuous change as rapid industrialization, urbanization, and economic growth is occurring at a fast pace. In previous studies, five factors have been identified to contribute significantly to PM 2.5 in Santiago de Chile: soil, motor vehicles, residual oil, sulfates and, to a smaller extent, in smaller contribution marine aerosols (Moreno et al, 2010). Regarding motor vehicles, about 42% of the Chilean vehicle fleet is concentrated in Santiago and it has also experienced a noticeable growth during the last five years (INE, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding motor vehicles, about 42% of the Chilean vehicle fleet is concentrated in Santiago and it has also experienced a noticeable growth during the last five years (INE, 2011). However, due to the stricter emission laws and improvements on vehicle technologies a decrease in the contribution of traffic has been noticed (Sax et al, 2007;Moreno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%